ANALISIS PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena L.) MENGGUNAKAN VARIETAS DAN JENIS PUPUK KOMPOS YANG BERBEDA DI DESA KRAKAL, ALIAN, KEBUMEN - Septia Khumaeroh; Rennanti Lunnadiyah Aprilia (Yayasan Nusantara Hasana Berdikari, 2025)
Eggplant is a popular horticultural crop in Indonesia due to its nutritional content and health benefits. According to data from BPS Kebumen Regency, eggplant production declined from 2020 to 2022. One of the ways to improve eggplant production is by using compost fertilizer. This study aims to determine the effect of different types of compost fertilizers on the growth and yield of eggplant (Solanum melongena L.) in different varieties. The research was conducted from September to December 2024 in Krakal Village. The method used was a factorial Complete Randomized Block Design (CRBD) with six treatments: Antaboga variety, Ratih Ungu variety, control, chicken manure compost, cow manure compost, and goat manure compost. Data analysis was performed using SPSS software, and if significant differences were found, the DMRT test at a 5% level was applied. The results showed that the Antaboga variety combined with cow manure compost produced the best results in several variables, including plant height (36.69 cm), fruit diameter (43.73 mm), fruit weight (143.63 g), and fruit length (22.50 cm). Meanwhile, the Ratih Ungu variety with goat manure compost showed the best results in plant height (44.12 cm), total fruit per plant (1.75 fruits), and fruit diameter (40.10 mm).